Cycad classification : concepts and recommendations (CABI, 2004)
This book presents the current state of our knowledge of the systematics of the approximately 300 species of cycads. It has been developed from 15 papers presented at the conference in Miami. Guidelines are presented for the designation of species, species boundaries and species groupings, thus clarifying what has been a confused area of research. Two appendices are included in this volume. The first gives details of the World List of Cycads at the time the manuscript for this volume was submitted to the publisher and is based on The Cycad Pages website of Sydney Royal Botanic Gardens. The second appendix provides a glossary of terms encountered in cycad systematics. This book will be of benefit to researchers in plant systematics and evolution, workers in conservation and horticulture, and to cycad enthusiasts throughout the world.